Flow Modelling in Porous Medium Applying Numerical Techniques: A Comparative Analysis - Sharma, Tejaskumar; Pathak, Shreekant; Trivedi, Gargi J; Sanghvi, Rajesh (Recent Research Reviews Journal, 2023)
This research paper presents a comprehensive comparative analysis of various numerical methods employed for simulating the flow of fluid in the porous medium. Porous media is crucial in numerous applications, including petroleum engineering, environmental science, and geology. Accurate modelling of flow in porous materials is essential for understanding and predicting the behaviour of fluids and contaminants. The study focuses on comparing the effectiveness and efficiency of different numerical methods in capturing the complex phenomena occurring in porous media. The results obtained from simulations using each method are analysed and discussed, highlighting their respective strengths and limitations. The findings of this research will aid researchers and practitioners in selecting appropriate numerical methods for their specific applications.
Keywords: Numerical methods; porous media; fluid flow; comparative analysis; simulation; computational efficiency; accuracy